Household food insecurity disease profile among underweight children aged between 6 and 60 months admitted to Potchefstroom hospital, North-West province - Ndagano, Baguma Jean-Claude (My University, 2019)
Introduction In South Africa, children aged between 6 and 60 months constitute a priority group considering that malnutrition remains a major health problem among them. Many studies have identified factors associated with undernutrition in different populations. One of these factors is food insecurity, defined by the fact that households do not have an adequate quantity of the right kind of foods necessary. Literature reports undernutrition as a major public health problem in developing countries, and many children die from its complications. In the researcher’s practice area of Potchefstroom, this is a serious problem which needs further clarification and attention. Aim: To explore household food insecurity and assess the disease profile among underweight children aged between 6 and 60 months admitted to the Potchefstroom Hospital. Methods This was a quantitative, observational cross-sectional study, conducted in the general paediatric ward at the Potchefstroom Hospital, North-West Province. A total of 100 parents or guardians of children aged between 6 to 60 months admitted from December 2016 to December 2017 were interviewed. Anthropometric measurements were taken and recorded. The household food insecurity access scale measurement tool of the Food and Agriculture Organisation was used to classify the households as food secure, insecure or at risk. Logistic regression was used to test the strength of association between food insecurity, disease profile and socio-demographic characteristics of the participants. Results The majority of participating children were female (54%, n=54), less than 24 months (88%, n=88), born in urban areas (61%, n=61). The majority of participants’ households had 2 children younger than 5 years (48%, n=48). Most of them were severely underweight (70%, n=70), HIV negative (81%, n=81), and had their immunisations up to date (63%, n=63). Most of the children came from families with food insecurity (96%) and were admitted with either acute gastroenteritis (46.0%, n=40) or lower respiratory tract infection (43.6%, n=38). In univariate analysis, immunisation status (p=0.019), acute diseases (p=0.042), household size (p=0.005) and number of children younger than 5 years in households (p=0.002) were found to be associated with food insecurity. Conclusion This study showed that food insecurity is highly prevalent among underweight children admitted to Potchefstroom Hospital and appears to underpin the acute gastroenteritis and lower respiratory tract infection in this setting. Household factors such as size and number of younger children were found mainly to be associated with food insecurity. These findings underscore the need for exploration of food security as part of the social context of under-5year old children who present to primary healthcare.
A research report submitted to the Faculty of Health Sciences In partial fulfillment of the requirements for the degree Of Master of Medicine in Family Medicine Department of Family Medicine University of the Witwatersrand